The implication of Brexit on Africa’s regional integration - Chwaro Koosentse; Thabang Motswaledi; Olerato Manyaapelo (Journal of BRICS Studies)
Brexit in contemporary International Relations has noticeable implications that Africa and other relating states should tentatively be on the lookout, as such the study contends that Britain leaving the European Union (EU) not only imposes negative attributes to African states, economically, politically, structurally and socially, but draws questionable attributes to the advocacy of Africa’s integration processes. Because of the diverse and multiple regional organizations, the study utilizes the African Union (AU) as an example to illustrate the impact Brexit will bear on regional institutions and equally impact on individual states’ quest to continue integrating with other states. The adoption of qualitative techniques is solely to assist the study in describing the impact of Brexit, both for states to learn to better their regional institutions or to advocate for national autonomy just as Britain is endeavoring. In assessing Africa’s perception amidst Brexit, the study holds that Britain’s endeavor for national autonomy threatens the principles of regional integration, as such, contributes significantly to the studying of Brexit’s multi-dimensional implications on Africa.